Use of Gamithromycin for the Treatment of Osteomyelitis Secondary to Foot Rot in a Sheep - Góss, Geórgia Camargo; Duarte, Claudia Acosta; Correa, Tiago Galinna; Machado, Ingrid Rios Lima; Mozzaquatro, Fabricio Desconsi; Rodrigues, Cláudia Medeiros; Prestes, Rafaela Silveira; Döwich, Gabriela (Acta Scientiae Veterinariae, 2018)
Background: Lameness is one of the main causes of economic losses in sheep breeding, especially in the distal region of the limbs. Poor sanitation management, especially in terms of hygiene conditions and the introduction of animals without previous preventive care, is an important predisposing factor in sheep flocks. Interdigital phlegmon (foot rot) is a bacterial disease that causes pain, heat, edema, hyperemia in the region, and can lead to secondary processes such as osteomyelitis. This case report describes the use of gamithromycin for the treatment of osteomyelitis secondary to foot rot in a sheep. Case: An Ile-de-France ewe exhibiting signs of lameness, pain, heat, hyperemia and edema in the four digits was treated at the Veterinary Hospital of UNIPAMPA. The lesions were characterized by interdigital phlegmon, commonly known as foot rot, and the right thoracic limb was more affected, exuding a foul odor and purulent secretion. The affected limbs were treated topically with an antiseptic solution. The lesions healed completely except for the right thoracic limb, whose clinical condition worsened. Osteitis was suspected, and was confirmed by radiographic evaluation of the region. Treatment with ceftiofur was introduced, but proved to be ineffective. Nevertheless, the lesion was found to have worsened, and a new X-ray evaluation was made, which revealed dislocation of the distal phalanx as well as involvement of the middle and proximal phalanges. Thus, we decided to perform chemical arthrodesis of the distal interphalangeal joint. Before beginning this procedure, contrast X-rays were taken that revealed the development of a fistulous pathway connecting the distal interphalangeal joint to the proximal interphalangeal joint, which precluded this procedure. In view of the worsening of the condition, amputation of the distal and middle phalanges was performed, as well as scraping of the distal edge of the proximal phalanx. In the postoperative period, ceftiofur was used as antibiotic therapy and flunixin meglumine as analgesic, in addition to daily dressings with topical iodine. After this procedure, there was no improvement in lameness and the radiographic images showed worsening of the clinical condition. At this time, the antimicrobial therapy was replaced with tylosin. After beginning treatment with this antimicrobial, there was a slight decrease in lameness, but a fistulous pathway with purulent secretion was formed in the region corresponding to the distal portion of the first phalanx, as well as an increase in the bone lesion, which was observed radiographically. Due to the ineffectiveness of the drug therapy, it was replaced by gamithromycin, which was applied three times. After beginning this treatment, lameness receded and the wound stopped producing purulent secretion, and at the end of the applications of this active ingredient, there was complete resolution of lameness and improvement of the radiographic signs of the animal of this case report. Discussion: Antimicrobial therapy is an important factor in the treatment of interdigital phlegmon and of osteomyelitis, and should be performed properly using broad-spectrum antibiotics. In the case reported here, although antibiotics with those characteristics were used, the active ingredient had to be changed more than once. In this particular case, there was an improvement in the lameness and the wound, and in the radiographic signs of the proximal phalanx, only after the application of gamithromycin. Therefore, this drug can be considered as an alternative for the treatment of osteomyelitis in ruminants, especially in cases unresponsive to treatment with other antibiotics.